Association of serum hemolytic complement levels with the major histocompatibility complex in chickens (The Rockefeller University Press, 1976)
The total hemolytic complement (C) levels in inbred line 7 chicks and adults were lower than C levels in inbred lines 2 and 3 and in outbred chickens of the same age. In all birds, adult levels of C were obtained in 5- to 6-wk-old chickens. Analysis of F1 and F3 generations clearly showed that the C level in chickens was determined by a dominant gene(s) associated with the major histocompatibility complex. Finding this association in a nonmammal strengthens the importance of the relationship between closely linked genes controlling histocompatibility, immune responsiveness, mixed leukocyte reaction, and C activity.